Collaborative Study of Thresholds for Mutagens: Adaptive Responses in the Micronucleus Test and Gene Induction by Mutagenic Treatments - Shizuyo Sutou; Akiko Koeda; Kana Komatsu; Toshiyuki Shiragiku; Hiroshi Seki; Toshiyuki Kudo (SAGE Publishing, 2024)
Background We have been conducting a collaborative study on the thresholds of mutagens. In our previous examinations of cell activity and cell proliferation as endpoints, both displayed hormesis. This time, we conducted experiments to determine thresholds using the micronucleus test as an endpoint. Methods The micronucleus test was conducted using Chinese hamster CHL/IU cells and mouse lymphoid L5178Y cells. Additionally, we conducted preliminary investigations into the gene expression using human TK6 cells. Results When adhesive CHL/IU cells were treated with mitomycin C (MMC), and the hormetic response was examined, hormesis was not observed clearly. When L5178Y cells were treated with methyl methanesulfonate (EMS), AF-2, MMC, and colchicine, all of them exhibited an adaptive response. Additionally, cross-adaptive responses using AF-2 and MMC or EMS and MMC were conducted, both combinations showed a cross-adaptive response. When the gene expression patterns of six genes were investigated by RT-PCR after treatment with MMC, EMS, and H 2 O 2 using TK6 cells, two genes, GADD45 A and P21 , were induced in a dose- and time-dependent manner. Conclusion Adaptive responses arise from preconditioning. As hormesis is inherently linked to preconditioning, adaptive responses observed in this study strongly suggest that hormesis was induced, hence existence of thresholds.